PENGARUH KARAKTERISTIK KEUANGAN TERHADAP FINANCIAL DISTRESS (Studi Empiris pada Perusahaan Sub Sektor Kesehatan dan Farmasi yang Terdaftar di Bursa Efek Indonesia) - Damayanti, Wan Mediasari (Jurusan Akuntansi FEB UNTAN, 2025)
Financial distress is a condition in which a company or individual has difficulty fulfilling its financial obligations. Independent variables used in this study are enterprise size, leverage, profitability, and sales growth. Meanwhile, the dependent variable in this study is the financial distress measured by the Interest Coverage Ratio (ICR). The research population is 31 health and pharmaceutical sub-sector companies listed on the Indonesia Stock Exchange (BEI) in 2018–2022. The sample determination was done using a purposive sampling method so that a population of 18 companies or 90 research samples was obtained. The research methods used in this study are descriptive analysis methods with logistic regression analysis and using SPSS version 25 aids. Research results show that the company size and sales growth variables do not offer a significant influence on financial distress. Meanwhile, leverage and profitability variables have a negative and significant effect on financial distress.